2012
DOI: 10.3141/2304-18
|View full text |Cite
|
Sign up to set email alerts
|

Probe Vehicles Used to Measure Road Ride Quality: Pilot Demonstration

Abstract: New vehicle technology is leading to efficient methods for assessing the condition of the National Highway System. The use of simple sensors such as accelerometers, installed in vehicles, could provide a cost-effective way to assess ride quality for pavement management. A pilot study compared data gathered from accelerometers with the current state-of-the-art practices for measuring ride quality. After a review of relevant previous studies involving probe vehicles, this study assessed the use of probe vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…In 2011, Flintsch et al conducted a pilot study using probe vehicles to measure road ride quality, or roughness (6). Again, vertical acceleration data were used as an index of vehicle vibration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Flintsch et al conducted a pilot study using probe vehicles to measure road ride quality, or roughness (6). Again, vertical acceleration data were used as an index of vehicle vibration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of simple sensors such as accelerometers, already installed either in vehicles or mobile devices, is able to measure the vibration responses of vehicles directly and is believed to correlate highly with pavement roughness. Several past efforts investigated the feasibility of collecting acceleration data to assess pavement roughness at a significantly lower cost and higher level of temporal resolution (3)(4)(5)(6). One critical issue about the acceleration-only index is that its value depends on a combined effect of vehicle operating speeds, vehicle dynamic features, and pavement characteristics (i.e., wavelength).…”
mentioning
confidence: 99%
“…Back-office systems would be responsible for further data processing, analysis, and storage. The technology required to implement crowdsourced pavement condition monitoring with smartphones is already established, and the concept has been shown to be technically feasible (3,5,15,16).…”
Section: Crowdsourcingmentioning
confidence: 99%
“…In addition, it has been reported that roughness characterizes energy consumption during the use phase from a life-cycle assessment view [ 11 ]. These facts justify why roughness measurements attract the interest of a Pavement Management System (PMS) [ 12 , 13 ]. Roughness is most often quantified in terms of the International Roughness Index (IRI, m/km), developed by the Word Bank in the mid-1980s as a standardized measurement method [ 14 ].…”
Section: Introductionmentioning
confidence: 99%